The Effect of Profitability, Liquidity, Asset Structure, and Dividend Policy on Capital Structure - Jihanu Tufahu; Menik Indrati (SIMAK, 2026)
This study aims to analyze the effect of profitability, liquidity, asset structure, and dividend policy on capital structure. This study uses a sample of 70 infrastructure sector companies listed on the Indonesia Stock Exchange for the 2020-2024 period. The research method used is quantitative and takes secondary data from annual reports, which are analyzed using panel data regression using Eviews12. The results show that profitability and asset structure do not significantly influence capital structure. Meanwhile, liquidity has a negative effect and dividend policy has a positive effect on capital structure. The conclusion of this study is that high profitability does not always reduce debt because the infrastructure sector requires large amounts of external funding. High liquidity actually has a negative effect on capital structure. The higher the liquidity, the lower the use of debt because the company is able to finance its needs with internal funds. Asset structure has not had a significant impact on capital structure, the large proportion of fixed assets is not always a primary consideration for companies in determining funding decisions through debt. Dividend policy has a positive effect on capital structure. The greater the dividends distributed, the greater the company's need for external funding, so the use of debt in the capital structure increases.